(untitled) (Docentes 2.0 Journal, 2019)
The aim of this research is to orient the textual production through teaching resources that will allow the students of fourth grade of the Institución Águeda Gallardo de Villamizar, Sede Jardín Nacional de Pamplona, be able to produce text after having produced a teaching material to demonstrate their capacity for imagination and organization of clear ideas, in order to foster psycho-social and human development. On the other hand, the research is developed from the very moment when the interest was aroused to know the recyclable material, the purpose was born to give it better use and to encourage in the students the creation and innovation. It is important that the teacher be creative and updated in the handling of the different materials to carry out each of these processes, it is necessary to have previous knowledge would lose the essence of class development. The materials to be worked with are clearly recyclable and should be economical for this process, because many students do not have the possibility to obtain them. It is pertinent that the teacher keeps within the classroom the pedagogical principles given by Flórez R. [1] allow to identify to the student community all the processes that are carried within the classroom of class indirectly.